EEF1Bγ binds the Che-1 and TP53 gene promoters and their transcripts. Issue 1 (December 2016) - Pisani, Cinzia; Onori, Annalisa; Gabanella, Francesca; Delle Monache, Francesca; Borreca, Antonella; Ammassari-Teule, Martine; Fanciulli, Maurizio; Di Certo, Maria; Passananti, Claudio; Corbi, Nicoletta
Abstract Background We have previously shown that the eukaryotic elongation factor subunit 1B gamma (eEF1Bγ) interacts with the RNA polymerase II (pol II) alpha-like subunit "C" (POLR2C), alone or complexed, in the pol II enzyme. Moreover, we demonstrated that eEF1Bγ binds the promoter region and the 3' UTR mRNA of the vimentin gene. These events contribute to localize the vimentin transcript and consequentially its translation, promoting a proper mitochondrial network. Methods With the intent of identifying additional transcripts that complex with the eEF1Bγ protein, we performed a series of ribonucleoprotein immunoprecipitation (RIP) assays using a mitochondria-enriched heavy membrane (HM) fraction. Results Among the eEF1Bγ complexed transcripts, we found the mRNA encoding the Che-1/AATF multifunctional protein. As reported by other research groups, we found the tumor suppressor p53 transcript complexed with the eEF1Bγ protein. Here, we show for the first time that eEF1Bγ binds not only Che-1 and p53 transcripts but also their promoters. Remarkably, we demonstrate that both the Che-1 transcript and its translated product localize also to the mitochondria and that eEF1Bγ depletion strongly perturbs the mitochondrial network and the correct localization of Che-1. In a doxorubicin (Dox)-induced DNA damage assay we show that eEF1Bγ depletion significantly decreases p53 protein accumulation and slightly impacts on Che-1 accumulation. Importantly, Che-1 and p53 proteins are components of the DNA damage response machinery that maintains genome integrity and prevents tumorigenesis. Conclusions Our data support the notion that eEF1Bγ, besides its canonical role in translation, is an RNA-binding protein and a key player in cellular stress responses. We suggest for eEF1Bγ a role as primordial transcription/translation factor that links fundamental steps from transcription control to local translation.